Two separate subtypes of early non-subplate projection neurons in the developing cerebral cortex of rodents - Espinosa, Ana; Gil-Sanz, Cristina; Yanagawa, Yuchio; Fairén, Alfonso (Frontiers in Neuroanatomy, 2009)
The preplate of the cerebral cortex contains projection neurons that connect the cortical primordium with the subpallium. These are collectively named pioneer neurons. After preplate partition, most of these pioneer neurons become subplate neurons. Certain preplate neurons, however, never associate with the subplate but rather with the marginal zone. In the present overview, we propose a novel classification of non-subplate pioneer neurons in rodents into two subtypes. In rats, the neurons of the first subtype are calbindin+, calretinin+ and L1+ and are situated in the upper part of the preplate before its partition. Neurons of the second subtype are TAG-1+ and are located slightly deeper to the previous population in the preplate. After the preplate partition, the calbindin+, calretinin+ and L1+ neurons remain in the marginal zone whereas TAG-1+ neurons become transiently localized in the upper cortical plate. In mice, by contrast, calcium binding proteins did not label pioneer neurons. We define in mice two subtypes of non-subplate pioneer neurons, either L1+ or TAG-1+/cntn2+. We propose these to be the homologues of the two subtypes of non-subplate pioneer neurons of rats. The anatomical distribution of these neuron populations is similar in rats and mice. The two populations of non-subplate pioneer neurons differ in their axonal projections. Axons of L1+ pioneer neurons project to the ganglionic eminences and the anterior preoptic area, but avoid entering the posterior limb of the internal capsule towards the thalamus. Axons of TAG-1+ pioneer neurons project to the lateral parts of the ganglionic eminences at the early stages of cortical histogenesis examined.